PENGARUH FINANCIAL LITERACY, LITERACY DIGITAL DAN E-COMMERCE TERHADAP KEBERLANGSUNGAN UMKM DI KECAMATAN MARPOYAN DAMAI - Hidayat, Wahyu; Linda, Roza (Jurnal Ekonomi Manajemen Bisnis Syariah dan Teknologi, 2024)
This research aims to determine the influence of Financial Literacy, Digital Literacy and E-commerce on Business Sustainability. The data collection method in this research uses primary data obtained from filling out questionnaires with 100 respondents from MSME actors in Marpoyan Peace District, Pekanbaru City. As well as secondary data obtained from literature books and journals related to this research. The data analysis methods used were data quality testing, classical assumption testing, multiple regression analysis and hypothesis testing. The results of this research show that the influence of Financial Literacy, Digital Literacy and E-commerce has a partial positive and significant effect on the Sustainability of MSME Businesses. Simultaneously, Financial Literacy, Digital Literacy and E-commerce have a significant effect on the sustainability of MSME businesses. The customized R Square value of 0.578 or 57.8% means that Financial Literacy, Digital Literacy and E-commerce have a positive and significant effect on Business Sustainability while the remaining 42.2% is influenced by other variables not included in this research.